2016
DOI: 10.7860/jcdr/2016/23577.9074
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease with Chilaiditi Syndrome

Abstract: A 70-year-old male with smoking history of 50 pack years presented to pulmonary medicine department with complaints of gradually progressive shortness of breath for last 3 years, chest discomfort and productive cough for last one month. General physical examination was within normal limits. Examination of the respiratory system revealed bilateral wheeze and bilateral basal crepitus.Routine haemogram, serum rheumatoid factor, anti-nuclear antibody levels and C-reactive protein were within normal limits. Sputum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has been suggested that there is a 4:1 male-to-female ratio incidence of Chilaiditi's sign [5]. This rare condition can mimic other more common conditions such as respiratory compromise, angina-like symptoms, nausea, vomiting, diarrhea, bowel obstruction, pneumoperitoneum, and abdominal pain [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there is a 4:1 male-to-female ratio incidence of Chilaiditi's sign [5]. This rare condition can mimic other more common conditions such as respiratory compromise, angina-like symptoms, nausea, vomiting, diarrhea, bowel obstruction, pneumoperitoneum, and abdominal pain [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…There are case reports of the syndrome with associated chronic lung conditions such as interstitial lung disease (ILD), COPD, and pulmonary malignancy. [ 9 10 ] These conditions are probably causing enlarged lower thoracic outlet after pushing the liver forward and downward, creating adequate space between the diaphragm and liver that facilitates the development of Chilaiditi sign. Once this sign develops, prevalent respiratory distress increases further due to reduced lung capacity.…”
Section: Discussionmentioning
confidence: 99%